Design, synthesis and biological evaluation of novel N-phosphorylated and O-phosphorylated tacrine derivatives as potential drugs against Alzheimer's disease - Maja Przybyłowska; Krystyna Dzierzbicka; Szymon Kowalski; Sebastian Demkowicz; Mateusz Daśko; Iwona Inkielewicz-Stepniak (Taylor & Francis Group, 2022)
In this work, we designed, synthesised and biologically investigated a novel series of 14 N- and O-phosphorylated tacrine derivatives as potential anti-Alzheimer's disease agents. In the reaction of 9-chlorotacrine and corresponding diamines/aminoalkylalcohol we obtained diamino and aminoalkylhydroxy tacrine derivatives. Next, the compounds were acid to give final products 6-13 and 16-21 that were characterised by 1H, 13 C, 31 P NMR and MS. The results of the docking studies revealed that the designed phosphorus hybrids, in theory can bind to AChE and BChE. All compounds exhibited significantly lower AutoDock Vina scores compared to tacrine. The inhibitory potency evaluation was performed using the Ellman's method. The most inhibitory activity against AChE exhibited compound 8 with an IC50 value of 6.11 nM and against BChE 13 with an IC50 value of 1.97 nM and they were 6- and 12-fold potent than tacrine. Compound 19 showed the lack of hepatocytotoxicity in MTT assay.